Heterochromia of the Iris, Skin Hypopigmentation and Hepatoblastoma Associated with Beckwith-Wiedemann Syndrome. Report of a Clinical Case with Long-Term Follow-Up - Pérez, Susana Portela; Cameselle-Cortizo, Lucía; Cruz, Teresa Calheiros; Rodríguez-Fernández, Vanesa; Dios, Pedro Diz; Pérez, Diana Valverde; Cameselle-Teijeiro, Jorge F (British Journal of Healthcare and Medical Research, 2023)
We describe the clinical case of a male diagnosed at birth with Beckwith-Wiedemann Syndrome (BWS). He was born prematurely (29 weeks) after a twin gestation, weighing 1,900 grams, and with severe macroglossia, mild omphalocele, bilateral inguinal hernia, and episodes of transient non-ketotic hypoglycemia in the neonatal period. In addition to the characteristic phenotype of BWS, he had bilateral heterochromia of the iris and hypopigmented skin macules on the skin of the abdomen and back. The genetic study confirmed the existence of an aberrant mutation of the H19 gene in the chromosomal region 11p15.5 and the paternal origin of the genetic alteration (paternal mosaicism). The patient was diagnosed at 5 months of age with hepatoblastoma that was resected at 9 months of age and received neoadjuvant chemotherapy. After 24 years of follow-up, there is clear aesthetic improvement in relation to complications derived from macroglossia, normal psychomotor development and no tumor recurrence.